2022
DOI: 10.3389/fpubh.2021.801273
|View full text |Cite
|
Sign up to set email alerts
|

Health Policy Development During COVID-19 in Saudi Arabia: Mixed Methods Analysis

Abstract: Healthcare systems are increasingly required to utilize effective approaches, apply evidence-based practice, and consequently sustain successful strategic management. Document analysis provides insights into the effective management tools applied by agencies to respond to crises. This article provides a practical exploration of how the Saudi health authority applied effective measures to eventually reduce the administrative and clinical consequences while managing the COVID-19 pandemic. The conceptual descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The occurrence of the COVID‐19 outbreak that recently happened in the early months of this 2020 led people throughout the world to extreme devastation, which included the healthcare systems of Saudi Arabia to come up with effective strategies, use evidence‐based practice and consequently sustain successful strategic management (Alonazi & Altuwaijri, 2022 ). The so‐called SARS‐CoV‐2 outbreak became a global widespread with the enormous, massive increase in mortality and morbidity rate of patient status that entails the world to be declared a ‘COVID‐19 state of the global pandemic’.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the COVID‐19 outbreak that recently happened in the early months of this 2020 led people throughout the world to extreme devastation, which included the healthcare systems of Saudi Arabia to come up with effective strategies, use evidence‐based practice and consequently sustain successful strategic management (Alonazi & Altuwaijri, 2022 ). The so‐called SARS‐CoV‐2 outbreak became a global widespread with the enormous, massive increase in mortality and morbidity rate of patient status that entails the world to be declared a ‘COVID‐19 state of the global pandemic’.…”
Section: Discussionmentioning
confidence: 99%
“…In yet another piece of research conducted by Al-Zalfawi et al, the population of Saudi Arabia was polled about their knowledge of vaccines, their feelings about getting vaccinated, and their thoughts on the COVID-19 vaccine. This was a questionnaire-based survey, and the study has reported that the people of Saudi Arabia are aware of the COVID-19 vaccination; however, they were observed to exhibit a fearful nature when it came to accepting the vaccine due to a lack of scientific evidence, which seems reasonable 12 . A cross sectional study by Al-Hanawi et al 13 has reported the similar results stating that the Saudi Arabian population are highly aware of COVID-19 and vaccination and positive attitude towards vaccine was also reported to be higher in average.…”
Section: The View Of Saudi Arabian People On Covid-19 Vaccinationmentioning
confidence: 99%
“…Data analysis is essential in assessing the available methods and whether they are effective. The COVID-19 virus emerged in late 2019 and has had deteriorating effects on most regions' socioeconomic status [6]. At first, healthcare facilities did not have specified disease management protocols.…”
Section: Strategies In Healthcare Facilities To Control Covid-19mentioning
confidence: 99%
“…The article reviewed in this section states various defining elements for an effective healthcare approach, including processes, health policies, context, and content. The Kingdom of Saudi Arabia was among the first regions to mitigate the spread of the disease before its occurrence [6]. This is because it had established early warning systems against diseases like COVID-19.…”
Section: Strategies In Healthcare Facilities To Control Covid-19mentioning
confidence: 99%